Shikara of the Rameshwar Temple - Ghosh, Ayan (2023)
Towering above the Banganga Tank is the weathered shikara of Rameshwar Temple, built in the North Indian Nagara style with amalaka (a stone disc in temple architecture) and kalash (an architectural element shaped like a metal pot with a large base and a narrow mouth) at the summit. Small figures of lions appear on the four sides of the shikara and there is a carving of Lord Shiva as Nataraja on its east face, facing the tank.